Eruptive angiokeratomas and porokeratosis in the setting of sclerodermatous graft‐vs.‐host disease. (15th April 2016) - Marks, Etan; Dorokhova, Olena; Amin, Bijal; Jacobson, Mark
Abstract : Porokeratosis and angiokeratomas are both seen in the setting of chronic graft‐vs.‐host disease (GVHD), but rarely occur together. We present a case of a patient with lichen planus‐like (LPL) and sclerodermatous chronic GVHD manifesting after allogeneic bone marrow transplant with concomitant eruptive angiokeratomas and porokeratosis.